Inner border making in Canada: Tracing gendered and raced processes of immigration policy changes between 2006 and 2015 - Nobe-Ghelani, Chizuru (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2017)
The Canadian immigration system went through significant changes under the previous Conservative government (2006–2015). This paper examines official narratives in the Citizenship and Immigration Canada (CIC) documents related to two policy changes: 1) Conditional permanent residency for the spousal sponsorship program, and 2) Bill C-43: Faster Removal of Foreign Criminals Act. Drawing on critical race readings of Canadian nation building and critical border literature that re-conceptualizes borders as processes, this paper examines the discursive narratives that enabled bordering processes to shift inward during the previous Conservative government era. My focus on the discursive processes and mechanisms sheds light on linkages between bordering practices and the historical construction of Canada as a white settler nation. I demonstrate the ways in which exclusionary policy developments constructed ‘inner borders’. I argue that the bordering practice at play in these policy changes were only possible through two discursive conditions and functions: 1) the naturalization of the gendered and racialized exclusions built into Canadian national membership, and 2) the erasure of historical and systemic injustice embedded in the Canadian immigration system and Canadian nation-building project as a whole. Through the naturalization and erasure of historical and systemic injustice, “inner borders” became “invisible borders, situated everywhere and nowhere” (Balibar, 2002, p. 78), pushing immigrant women and the racialized community into further precariousness.